Visual orientation uncertainty in the rod-and-frame illusion - Pomante, Antonella; Selen, Luc P. J.; Medendorp, W. Pieter (Journal of vision (Charlottesville, Va.), 2019)
Estimation of the orientation of the head relative to the earth's vertical is thought to rely on the integration of vestibular and visual cues. The role of visual cues can be tested using a rod-and-frame task in which a global visual scene, typically a square frame, is displayed at different orientations together with a rod whose perceived direction is a proxy for the head-in-space estimate. While it is known that the frame biases this percept, and hence the subjective visual vertical, the possible role of the rod itself in this processing has not been examined. Current models about spatial orientation assume that the visual orientation of the rod and its uncertainty play no role in the visual-vestibular integration process, but are only involved in the transformation that yields rod orientation in space, thereby contributing additive noise to the subjective visual vertical. Here we tested the validity of this assumption in the rod-and-frame task by replacing the rod with an ellipse whose orientation uncertainty was manipulated by varying its eccentricity (i.e., making the ellipse more or less rounded). Using a psychophysical approach, subjects performed this ellipse-and-frame task for three different eccentricities of the ellipse (0.74, 0.82, 0.99) and three frame orientations (-17.5°, 0°, 17.5°). Results show that ellipse eccentricity affects the uncertainty but not the bias of the subjective visual vertical, suggesting that the ellipse does not interact with the frame in global visual processing but contributes additive noise in computing its orientation in world coordinates.